Edukasi Slow Deep Breathing pada Akseptor KB IUD di Klinik Ibnu Sina Rapak Balikpapan - Purba, Endang Onalisa; Juhriani; Sari, Kartika (Prosiding Seminar Nasional dan CFP Kebidanan Universitas Ngudi Waluyo, 2024)
Use of the contraceptive device IUD (Intra Uterine Device) in new birth control acceptors who are installed after delivery. An IUD, or spiral, is a small object made of flexible plastic that has a copper coil or also contains hormones, is inserted into the uterus through the vagina, and has threads. Increasing the use of IUDs will reduce the number of unwanted pregnancies in the future, thereby reducing maternal and infant mortality rates in Indonesia. Several factors that influence anxiety in IUD family planning acceptors are: age, physical condition, social culture, education, and knowledge. There are quite a lot of side effects from the IUD, such as expulsion, infection, and perforation. This is what makes the mother feel afraid and anxious; the anxiety felt by the mother can have an impact on the mother's psychology. One method to reduce anxiety in IUD contraceptive acceptors is slow, deep breathing. The aim of this community service is to increase knowledge of IUD family planning acceptors and calm, slow, deep breathing through health education. The method of community service activities is to provide material to 30 mothers of toddlers through interactive lectures and discussions. To evaluate the mother's knowledge, ask the IUD family planning acceptor about slow, deep breathing. From the results of the activity, it was found that there was an increase in the knowledge of IUD family planning acceptors about slow deep breathing at the Ibnu Sina Rapak Clinic in Balikpapan, and they were able to practice slow deep breathing. It is hoped that by increasing knowledge of IUD family planning acceptors, they will be able to carry out slow, deep breathing properly and correctly in order to reduce the level of anxiety in IUD family planning acceptors.   Abstrak Penggunaan alat kontrasepsi IUD (Intra Uterine Device) pada akseptor KB baru yang dipasang pasca persalinan.AKDR atau IUD atau spiral adalah suatu benda kecil yang terbuat dari plastik yang lentur, mempunyai lilitan tembaga atau juga mengandung hormon dan dimasukkan kedalam rahim melalui vagina dan mempunyai benang. Peningkatan penggunaan IUD akan dapat mengurangi jumlah kehamilan yang tidak diinginkan dimasa depan, sehingga akan mengurangi angka kematian ibu dan bayi di Indonesia. Beberapa faktor yang mempengaruhi kecemasan pada akseptor KB IUD adalah: usia, keadaan fisik, sosial budaya, pendidikan dan pengetahuan. Efek samping yang terdapat pada IUD memang cukup banyak seperti ekspulsi, infeksi, perforasi, Hal inilah yang membuat ibu merasa takut dan merasa cemas, dengan adanya cemas yang dirasakan oleh ibu ini bisa berdampak pada psikologis ibu. Salah satu metode untuk menurunkan kecemasan pada akseptor KB IUD adalah dengan slow deep breathing. Tujuan pengabdian masyarakat ini untuk meningkatkan pengetahuan akseptor KB IUD tenang slow deep breathing melalui penyuluhan kesehatan. Metode kegiatan pengabdian masyarakat yaitu memberikan materi kepada 30 ibu yang memiliki balita melalui ceramah interaktif dan diskusi. Untuk mengevaluasi pengetahuan ibu yaitu dengan bertanya kepada akseptor KB IUD tersebut tentang slow deep breathing. Dari hasil kegiatan diperoleh terjadi peningkatan pengetahuan akseptor KB IUD tentang slow deep breathing di Klinik Ibnu Sina Rapak Balikpapan sudah bisa mempraktekkan slow deep breathing. Diharapkan dengan adanya peningkatan oengetahuan akseptor KB IUD dapat melakukan slow deep breathing yang baik dan benar, agar dapat menunrunkan tingkat kecemasan pada akseptor KB IUD.